The Top 100 Most-Cited Papers on Intravitreal Injections: A Bibliographic Perspective - Nov E (Dove Medical Press, 2020)
Eytan Nov,1 Elad Moisseiev1,2 1Department of Ophthalmology, Meir Medical Center, Kfar Saba, Israel; 2Sackler School of Medicine, Tel Aviv University, Tel Aviv, IsraelCorrespondence: Elad Moisseiev Department of OphthalmologyMeir Medical Center, 59 Tshernichovsky Street, Kfar Saba 4428164, IsraelTel +97297471527Fax +97297472427Email elad_moi@netvision.net.ilPurpose: To analyze the top 100 most-cited papers on pars intravitreal injections.Methods: Literature search using the bibliographic databases of the ISI Web of Knowledge for all types of publications on intravitreal injections published between 1965 and 2019 in peer-reviewed journals.Results: Eighty-three of the top 100 papers on intravitreal injections were published in ophthalmology journals, their majority in the top five Q1 leading journals in the field. They originated from 16 different countries, predominantly from the USA (n=52), and were all published in English. These manuscripts cover a wide spectrum of topics but were mostly focused on retinal diseases (n=60) and the use of anti-VEGF or steroid agents (n=75).Discussion: This bibliographic study provides a unique perspective on the evolution and assimilation of intravitreal injections, from their introduction, through their present role as the most common therapeutic procedure in ophthalmology, to future developments.Keywords: bibliography, citation, historical, intravitreal injection